Late-Onset Posttransplant Lymphoproliferative Disorder Results in Jejunal Stricture Managed with Endoscopic Dilation - Steven Park; John Miller; Janice Cheong; Asad Ullah; Lawrence Saubermann; Arthur Decross (Case Reports in Gastrointestinal Medicine)
Background. Late-onset posttransplant lymphoproliferative disorder (PTLD) after orthotopic heart transplantation is rare. Case Presentation. We present a rare diagnosis of small bowel stricture caused by healed lymphomatous ulcers in a patient with orthotopic heart transplantation and PTLD diagnosed 25 years after initial transplantation. We also demonstrate successful endoscopic balloon dilations that improved the patient’s obstructive symptoms. Conclusion. It is important to consider stricture from healed lymphomatous ulcers in posttransplant patients presenting with obstructive symptoms.